Round the year fodder production model for small and marginal farmers of Bihar - Kumar, Dharmendra; Bhadauria, Pragya; Kumar, Anjani; Kumar, Rajesh; Sohane, R K (Indian Farming, 2024)
Bihar relies heavily on agriculture as its primary source of wealth, playing a crucial role in the overall development of the state's economy. The state government has given utmost priority to the advancement of agriculture. However, the insufficiency of fodder and feed resources in the state has been acknowledged and articulated on numerous occasions. A shortage of feed and fodder standsas a significant obstacle to sustainable livestock development in the state, directly impacting the income and livelihoods of numerous resource-poor livestock keepers. Various constraints, such as the scarcity of feed, fodder, and concentrates, hinder the potential of livestock, leading to substantial losses in terms of production and depletion of livestock resources. In view of this, KVK Banka haspromoted village based round the year fodder production model by integrating various approaches to overcome the shortage of fodder and ensuring a consistent supply of green fodder throughout the year for livestock keepers. It has been observed that integrating more green fodder into animal diets has the potential to lower milk production costs. Also, many farmers start relying on common property resources to fulfil their animals' fodder needs after intervention by the KVK.